Antithrombotic stewardship: a multidisciplinary team approach towards improving antithrombotic therapy outcomes during and after hospitalisation: a study protocol. Issue 12 (20th December 2016) - Dreijer, Albert R; Kruip, Marieke J H A; Diepstraten, Jeroen; Polinder, Suzanne; Brouwer, Rolf; Leebeek, Frank W G; Vulto, Arnold G; van den Bemt, Patricia M L A
Abstract : Introduction: Antithrombotic therapy carries high risks for patient safety. Antithrombotics belong to the top 5 medications involved in potentially preventable hospital admissions related to medication. To provide a standard for antithrombotic therapy and stress the importance of providing optimal care to patients on antithrombotic therapy, the Landelijke Standaard Ketenzorg Antistolling (LSKA; Dutch guideline on integrated antithrombotic care) was drafted. However, the mere publication of this guideline does not guarantee its implementation. This may require a multidisciplinary team effort. Therefore, we designed a study aiming to determine the influence of hospital-based antithrombotic stewardship on the effect and safety of antithrombotic therapy outcomes during and after hospitalisation. Methods and analysis: In this study, the effect of the implementation of a multidisciplinary antithrombotic team is compared with usual care using a pre-post study design. The study is performed at the Erasmus University Medical Center Rotterdam and the Reinier de Graaf Hospital Delft. Patients who are or will be treated with antithrombotics are included in the study. We aim to include 1900 patients, 950 in each hospital. Primary outcome is the proportion of patients with a composite end point consisting of ≥1 bleeding or ≥1 thrombotic event from the beginning of antithrombotic therapy (or hospitalisation) until 3 months after hospitalisation. Bleeding is defined according to the International Society of Thrombosis and Haemostasis (ISTH) classification. A thrombotic event is defined as any objectively confirmed arterial or venous thrombosis, including acute myocardial infarction or stroke for arterial thrombosis and deep venous thrombosis or pulmonary embolism or venous thrombosis. An economic evaluation is performed to determine whether the implementation of the multidisciplinary antithrombotic team will be cost-effective. Ethics and dissemination: This protocol was approved by the Medical Ethical Committee of the Erasmus University Medical Center. The findings of the study will be disseminated through peer-reviewed journals and presented at relevant conferences. Trial registration number: NTR4887 ; pre-results.